Exploring textbooks and cultural change in Nordic education 1536-2020 - Roos, Merethe 1971-; Berge, Kjell Lars; Edgren, Henrik; Hiidenmaa, Pirjo; Matthiesen, Christina (Brill Sense, 2021)
"This volume addresses a gap in previous research and explores Nordic textbooks chronologically and empirically from the Protestant Reformation to our present time. The chapters are written by scholars from universities in Finland, Denmark, Sweden and Norway, countries that distinguish themselves with a rich tradition of textbook research. The authors represent different academic traditions and use a wide range of scholarly methods and perspectives. The overall objective is to highlight how textbooks reflect national cultural politics and legislation. The various chapters cast light on how textbooks are integrated in national politics and demonstrate how they have contributed to nation-building and to strengthening the nations' core values and other major political projects. Contributors are: Karl Christian Alvestad, Norunn Askeland, Kjell Lars Berge, Peter Bernhardsson, Kerstin Bornholdt, Mads B. Claudi, Henrik Edgren, Morten Fink-Jensen, Stig Toke Gissel, Thomas Illum Hansen, Pirjo Hiidenmaa, Marthe Hommerstad, Axel Hörstedt, Kari-Anne Jørgensen-Vittersø, Tujia Laine, Esbjörn Larsson, Ragnhild Elisabeth Lund, Christina Matthiesen, Eva Maagerø, Tuva Skjelbred Nodeland, Kari H. Nordberg, Merethe Roos, Henriette Hogga Siljan, Johan Laurits Tønnesson and Janne Varjo"--